Noninvasive Aortic Ultrafast Pulse Wave Velocity Associated With Framingham Risk Model: in vivo Feasibility Study - Kang, Jinbum; Han, Kanghee; Hyung, Jihyun; Hong, Geu-Ru; Yoo, Yangmo (Frontiers in Cardiovascular Medicine, 2022)
Background: Aortic pulse wave velocity (PWV) enables the direct assessment of aortic stiffness, which is an independent risk factor for cardiovascular (CV) events. The aim of this study was to evaluate the association between aortic PWV and CV risk model classified into three groups based on the Framingham risk score (FRS): low-risk (<10%), intermediate-risk (10%–20%), and high-risk (>20%). Methods: To noninvasively estimate local PWV in the abdominal aorta, a high-spatiotemporal resolution PWV measurement method (>1 kHz) based on wide field-of-view ultrafast curved array imaging (ufcPWV) was proposed. In the ufcPWV measurement, a new aortic wall motion tracking algorithm based on an adaptive reference frame update was performed to compensate for errors from the temporally accumulated out-of-plane motion. In addition, an aortic pressure waveform was simultaneously measured by applanation tonometry, and a theoretical PWV based on the Bramwell-Hill model (bhPWV) was derived. A total of 69 participants (aged 23 to 86 years) according to the CV risk model were enrolled and examined with an abdominal ultrasound scan. Results: The ufcPWV was significantly correlated with bhPWV (r = 0.847, p <0.01), and it showed a statistically significant difference between low- and intermediate-risk (5.3 ± 1.1 vs. 8.3 ± 3.1 m/s, p <0.01), and low- and high-risk groups (5.3 ± 1.1 vs. 10.8 ± 2.5 m/s, p <0.01), while there was no significant difference between the intermediate- and high-risk groups (8.3 ± 3.1 vs. 10.8 ± 2.5 m/s, p = 0.121). Moreover, the ufcPWV showed a significant difference between two evaluation groups (low- (<10%) vs. higher-risk group (≥10%), 5.3±1.1 vs. 9.4±3.1 m/s, p <0.01) when the intermediate- and high-risk groups were merged into a higher-risk group. Conclusion: This feasibility study based on the CV risk model demonstrated that the aortic ufcPWV measurement has the potential to be a new approach to overcome the limitations of conventional systemic measurement methods in the assessment of aortic stiffness.